Root-colonizing bacteria enhance the levels of (E)-β-caryophyllene produced by maize roots in response to rootworm feeding - Chiriboga, Xavier; Huijuan, Guo; Campos Herrera, Raquel; Röder, Gregory; Imperiali, Nicolas; Keel, Christoph; Maurhofer, Monika; Turlings, Ted (My University, 2018)
When larvae of rootworms feed on maize roots they induce the emission of the sesquiterpene (E)-β-caryophyllene (EβC). EβC is attractive to entomopathogenic nematodes, which parasitize and rapidly kill the larvae, thereby protecting the roots from further damage. Certain root-colonizing bacteria of the genus Pseudomonas also benefit plants by promoting growth, suppressing pathogens or inducing systemic resistance (ISR), and some strains also have insecticidal activity. It remains unknown how these bacteria influence the emissions of root volatiles. In this study, we evaluated how colonization by the growth-promoting and insecticidal bacteria Pseudomonas protegens CHA0 and Pseudomonas chlororaphis PCL1391 affects the production of EβC upon feeding by larvae of the banded cucumber beetle, Diabrotica balteata Le Conte (Coleoptera: Chrysomelidae). Using chemical analysis and gene expression measurements, we found that EβC production and the expression of the EβC synthase gene (tps23) were enhanced in Pseudomonas protegens CHA0-colonized roots after 72 h of D. balteata feeding. Undamaged roots colonized by Pseudomonas spp. showed no measurable increase in EβC production, but a slight increase in tps23 expression. Pseudomonas colonization did not affect root biomass, but larvae that fed on roots colonized by P. protegens CHA0 tended to gain more weight than larvae that fed on roots colonized by P. chlororaphis PCL1391. Larvae mortality on Pseudomonas spp. colonized roots was slightly, but not significantly higher than on non-colonized control roots. The observed enhanced production of EβC upon Pseudomonas protegens CHA0 colonization may enhance the roots' attractiveness to entomopathogenic nematodes, but this remains to be tested.
Keywords: Diabrotica balteata Entomopathogenic nematodes Root-colonizing bacteria (E)-β -caryophyllene